PUBLIC WORKS CONCESSIONS - DELIMITATION FROM OTHER CONTRACTS - CATALINA-GEORGETA MATEI; ROXANA-ANCA ADAM (Annals of the University of Petrosani: Economics, 2012)
Initially in France the judicial basis of contracts concerning the occupancy of public domain was the Law of 17 June 1938, but also art. L 84 of the Domain’s Code (1790), as well as a number of relevant decisions of the State Council. Some of the contracts concerning the occupancy of public domain are the funeral contracts and certain public works or railway concession contracts. Other contracts are applicable to domain areas not affected by this type of occupancy, namely the public domain destined for public use, like concessions of public road services or of maritime fishing institutions. The distinction is significant, as in dedicated contracts, like the funeral concession, the occupant’s utilization and disposition rights are considerably wider than in the case of contracts of general interest.